Whole-Genome Identification and Analysis of Carbohydrate Esterase Gene Family in Colletotrichum graminicola - Wenting Zhu; Limin Wang; Honglian Li; Yan Shi; Jiaxin Chang; Senbo Wang; Xu Liu; Penghao Ma; Jinzhang Zhao; Yan Liu; Yafei Wang (Agriculture)
Colletotrichum graminicola can cause leaf spots and stalk rot in maize. The primary function of carbohydrate esterases (CEs) is to eliminate ester modifications from monosaccharides, oligosaccharides, and polysaccharides, thereby facilitating the hydrolysis of sugars. We identified 128 CE genes through whole-genome analysis and functional annotation of C. graminicola TZ–3 here. We further analyzed the physicochemical properties, subcellular localization, conserved motifs, gene structures, promoter regulatory elements of these 128 C. graminicola CE (CgCE) genes. Our results indicated that half of the CgCE proteins were located extracellularly. The CgCE proteins demonstrated diversity in both their structures and motifs. Furthermore, the CgCE gene family contained numerous conserved domains, suggesting potential functional diversity. Regulatory elements associated with various stresses and plant hormones were identified in this study. GO enrichment and expression pattern analysis indicated that the CgCE genes were involved in metabolic processes and might contribute to the establishment of fungal infections and lesion expansion. These results enhance our understanding of the CE family genes in C. graminicola and provide a foundation for further investigations into their roles in fungal pathogenesis.